2022
DOI: 10.1101/2022.01.28.22269989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic Three-Dimensional Cephalometric Landmarking via Deep Learning

Abstract: The increasing use of three-dimensional (3D) imaging by orthodontists and maxillofacial surgeons to assess complex dentofacial deformities and plan orthognathic surgeries implies a critical need for 3D cephalometric analysis. Although promising methods were suggested to localize 3D landmarks automatically, concerns about robustness and generalizability restrain their clinical use. Consequently, highly trained operators remain needed to perform tedious manual landmarking. In this study, we aimed to train and ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results of studies comparing artificial intelligence (AI) and traditional cephalometric analysis vary. Some authors highlight numerous advantages of AI, such as increased convenience, shorter analysis time, and high accuracy [48,53]. For instance, a study by Wang et al [54] suggests that AI analysis demonstrates high precision, with deviations of up to 2 mm, and a detection rate of up to 80%.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The results of studies comparing artificial intelligence (AI) and traditional cephalometric analysis vary. Some authors highlight numerous advantages of AI, such as increased convenience, shorter analysis time, and high accuracy [48,53]. For instance, a study by Wang et al [54] suggests that AI analysis demonstrates high precision, with deviations of up to 2 mm, and a detection rate of up to 80%.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Description of the sample characteristics (e.g., age, gender, craniofacial characteristics) was not provided by all the articles. Only eight studies [29,[34][35][36][37][38][39][40] indicated the execution time of Fig. 1 Prisma flowchart for the papers' selection process the identification system, and four of them [34,36,38,39] also reported the duration of the training phase.…”
Section: Study Selection and Qualitative Analysismentioning
confidence: 99%
“…Only eight studies [29,[34][35][36][37][38][39][40] indicated the execution time of Fig. 1 Prisma flowchart for the papers' selection process the identification system, and four of them [34,36,38,39] also reported the duration of the training phase.…”
Section: Study Selection and Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the testing dataset was significantly low in this experiment. Dot et al (2022) has performed DL-based experiment for automatic cephalometric landmark detection. Thirty-three landmarks were plotted automatically on 38 testing images to demonstrate the accuracy of the method.…”
Section: Introductionmentioning
confidence: 99%